KAJIAN KARAKTERISTIK MORFOLOGI PISANG TONGKA LANGIT DI KOTA AMBON PROVINSI MALUKU - Marlita H Makaruku; Anna Y Wattimena; Vilma L Tanasale; Jeanne I Nendissa (Pattimura Proceeding, 2022)
Indonesia has a lot of germplasm diversity, one of which is the banana plant. Tongka Langit banana plant (Musa troglodytarum L.) is a type of banana endemic to eastern Indonesia, namely Maluku and Papua, which is quite unique. Morphological characterization is an approach used to identify a plant. In banana plants, characterization was carried out in the vegetative and generative phases which included the characters of leaves, stems, flowers and fruit. The method used in this research is a survey and direct observation at the research site. Based on the results of observations, it can be concluded that there is variation in the leaf character, while the flower and fruit characters for the two research locations show no variation